PEMENUHAN KEBUTUHAN SUAMI DAN ISTRI DALAM KELUARGA RASULULLAH PRESFEKTIF AL-QURAN DAN HADIST - Abidin, Zainul; Zainul Abidin, Muhamad (LPPM IAIT, 2025)
This article explores the fulfillment of marital needs in the household of Prophet Muhammad ﷺ as an ideal model for establishing a harmonious and value-based Islamic family. The study focuses on three main dimensions: emotional needs, spousal relational closeness, and spiritual tranquility. Prophet Muhammad ﷺ exemplified gentle communication, sincere affection, and emotional warmth in his interactions with his wives. Regarding the intimate marital relationship, the Prophet emphasized mutual understanding, refined manners, and attentiveness to the partner’s well-being. This study adopts a qualitative descriptive approach through library research, drawing on primary sources such as the Qur’an and hadith, along with relevant scholarly literature. The findings aim to contribute to the discourse on Islamic marital ethics that emphasize cooperation, compassion, and emotional balance within the family.